Strategi Jam’iyatul Qurro’ dalam Mengembangkan Soft Skill Santri di Pondok Pesantren Riyadlus Sholihin - Sholihin, M.; Khoiriyah, Khoiriyah (YASIN, 2025)
This study aims to explore the strategies employed by Jam’iyatul Qurro’ in developing the soft skills of santri at Pondok Pesantren Riyadlus Sholihin. It specifically analyzes the approaches implemented by Jam’iyatul Qurro’ in shaping the social skills of santri and identifies both the impacts and challenges associated with these strategies. By adopting a group-based approach and encouraging the active participation of santri in various activities, Jam’iyatul Qurro’ has successfully fostered an environment that promotes collaboration and mutual respect two essential components in the development of santri’s soft skills. This study employs a descriptive qualitative approach with a case study design. Data collection is conducted through three primary techniques: interviews, observations, and documentation. The collected data is analyzed using the Miles and Huberman model, which involves data collection, data reduction, and data presentation in alignment with the observed phenomena. The findings of this study indicate that the strategies implemented by Jam’iyatul Qurro’ at Pondok Pesantren Riyadlus Sholihin play a crucial role in enhancing santri’s soft skills, particularly in interpersonal and leadership competencies. Based on insights gathered through interviews and observations, it is evident that activities such as group discussions, leadership training, and group-based learning methods have effectively created a conducive environment for developing santri’s social skills.